Hubungan Pola Asuh Orang Tua dengan Prestasi Belajar Siswa MTS. Assulamy Langko - Rani, Yulia Viza; Ariyanto, Mustaqim Setyo; Fildzah Malahati (EduInovasi: Journal of Basic Educational Studies, 2025)
Learning achievement is the result of learning obtained by students while carrying out school learning. The purpose of this study is to determine how much influence parenting patterns have on their children's learning achievement. This study uses quantitative methods with spearman rank analysis. Respondents in this study were 93 students in class VII and class VIII MTs. Assulamiy Langko. The results of the study are a positive relationship with a significance value of 0.036, meaning that the better the parenting style given by parents, the higher the learning achievement obtained by students.